Assessing Public Transit Network Efficiency and Accessibility in Johor Bahru and Penang, Malaysia: A Data-Driven Approach - Mahbub Hassan; Hridoy Deb Mahin; Ferdoushi Ahmed; Md. Maruf Hassan; Atikur Rahaman; Masuk Abdullah (Results in Engineering, 2025)
This study conducts a comprehensive analysis of public bus transit networks in Johor Bahru and Penang, Malaysia, using General Transit Feed Specification (GTFS) data. It focuses on evaluating network efficiency, spatial equity, and accessibility within the myBAS Johor and Rapid Bus Penang systems. As the first academic application of Malaysia’s newly released GTFS Static datasets, this research develops an integrated methodological workflow that combines GTFS with OpenStreetMap points of interest, global walking friction surfaces, and population density rasters. The analysis employs graph-theoretic centrality metrics, kernel density estimation, the Jaccard Similarity Index, and raster-based cost surface modeling to assess transit performance across structural, spatial, and temporal dimensions. Graph-based network analysis identify key urban hubs—such as Larkin Sentral in Johor Bahru and Terminal Komtar in Penang—as critical nodes for multimodal connectivity and efficient passenger transfers. Notable spatial inequities remain, with suburban and peripheral areas facing limited transit coverage, long walking distances, and poor access to key services like healthcare, education, and commerce. Service frequency drops significantly during off-peak hours, restricting mobility for transit-dependent users. Additionally, route overlap in dense urban corridors contrasts with inadequate service in outer areas, revealing operational inefficiencies. To address these challenges, the study recommends expanding stop coverage in underserved regions, optimizing route configurations in high-demand corridors, and piloting demand-responsive transit services to enhance adaptability and inclusivity. Beyond its contributions to Malaysian transport planning, the research offers a replicable, open-data-driven approach that can inform transit modernization efforts in cities undergoing digital transitions in transit network management and accessibility planning.